The influence of work environment, compensation and work motivation on employee performance at PT. BRALING WISNU SATRIYA Purbalingga - Yudi Agus Setiawan; Dina Prasetyaningrum (STIE Binaniaga, 2020)
The aim of this research was to determine and analyze the influence of the Work Environment, Compensation, and Work Motivation on the performance of the employees of PT Braling Wisnu Satriya Purbalingga. The hypotheses of this research are 1) Work environment has a significant effect on employee performance at PT Braling Wisnu Satriya Purbalingga, 2) Compensation has a significant effect on employee performance at PT Braling Wisnu Satriya Purbalingga, 3) Work motivation has a significant effect on employee performance at PT Braling Wisnu Satriya Purbalingga. To test the effect of the independent variable on the dependent variable, multiple linear regression analysis was used, and based on the results of the analysis, the t₁ value was 2.653, t₂ was 4.682, t was 2.627 and each t was greater than t table (1.672), which means that Ho rejected or Ha accepted, so based on the t test, the first, second, and third hypotheses are accepted. Keywords: Work Environment, Compensation, Work Motivation, Employee Performance